Obesity status trajectory groups among elementary school children - Chen, Tzu-An (BMC Public Health, 2016)
BACKGROUND: Little is known about patterns in the transition from healthy weight to overweight or obesity during the elementary school years. This study examined whether there were distinct body mass index (BMI) trajectory groups among elementary school children, and predictors of trajectory group membership. METHODS: This is a secondary analysis of 1651 elementary school children with complete biannual longitudinal data from kindergarten to the beginning of 5(th) grade. Heights and weights were measured by trained school nurses using standard procedures at the beginning and end of each school year for 11 consecutive assessments. Group-based trajectory clustering and multinomial logit modeling were conducted. RESULTS: When using BMIz score, six trajectory groups were identified revealing substantial consistency in BMIz score across time. When using a categorical variable separating overweight/obese children (BMI ≥ 85%ile) from the rest, five developmental trajectories (persistently non-overweight/obese weight: 51.1 %; early-onset overweight/obese: 9.2 %; late-onset overweight/obese: 9.7 %; becoming healthy weight: 8.2 %; and chronically overweight/obese: 21.8 %) were identified. When using a categorical variable separating obese children (BMI ≥ 95%ile) from the rest, three trajectories (persistently non-obese: 74.1 %, becoming obese: 12.8 %; and chronically obese: 13.2 %) were identified. For both cutoffs (≥ BMI percentile 85 % or 95 %), girls were more likely than boys to be classified in the persistently non-overweight and/or obese group (odds ratios (OR) ranged from 0.53 to 0.67); and Hispanic children and non-Hispanic Black children were more likely to be chronically overweight and/or obese than non-Hispanic White children (OR ranged from 1.57 to 2.44). Hispanic children were also more likely to become obese (OR: 1.84) than non-Hispanic White children when ≥ BMI percentile 95 % was used. CONCLUSIONS: Boys, Hispanic and non-Hispanic Black children were at higher risk of being overweight or obese throughout their elementary school years, supporting the need for obesity treatment. Post kindergarten and post second grade summer months were times when some children transitioned into overweight/obesity. It will be important to identify which behavioral factors (e.g., diet, physical activity, sedentary behaviors, and/or sleep) predisposed children to becoming overweight/obese, and whether these factors differ by time (Kindergarten versus second grade). If behavioral predisposing factors could be identified early, targeted obesity prevention should be offered.